Effect of Using Functional Impression Technique on Fit Accuracy of Removable Partial Dentures. (Journal of Hama University, 2022)
Several studies have reported many cases of inaccuracy fit of cobalt- chromium metal framework's major connectors. The functional impression technique, introduced and described by many authors, is considered one of high-pressure impression techniques. The choice of final impression technique plays a role in determining the amount of tissue pressure under removable partial denture. Therefore, this may affect the accuracy fit of denture on its supporting tissues. The purpose of this research is to study the effect of using functional impression technique on fit accuracy of removable partial dentures.: A total of ten maxillary Kennedy's first-class partially edentulous patients were included in the research. Two identical metal frameworks were made for each patient on two master casts, one resulting from a final functional impression, and the other from a final static impression.A low-viscosity polyvinylsiloxane was put on the opposite surface of tissues of the metal framework. Then the metal framework was inserted into the patient mouth. A polyvinylsiloxane flake was cut from the mid palatal area with dimensions (1x2) cm, and with distance of 5 mm from the denture posterior edge. The polyvinylsiloxane flakes resulted was weighted and data were analyzed using t-student test as (P < .05).Within the limitations of the current study, it is possible to say that the accuracy of fit of RPD frameworks of functional impression is better than RPD frameworks of static impression. We recommend the use of the functional impression technology when making the final impressions of maxillary Kennedy's first-class removable partial dentures to obtain better accuracy fit of removable partial denture on its supporting tissues.